DIGITAL MARKETING PRACTICES IN MOROCCAN SMES (SMALL AND MEDIUM SIZED ENTERPRISES): A SYSTEMATIC LITERATURE REVIEW - LOUBNA HARAMOUNI; ELKANDOUSSI FATIMA; SKOURI HASSAN (Revue Marocaine de Recherche en Management et Marketing, 2023)
The digital era offers Small and Medium-Sized Enterprises (SMEs) opportunities to grow and even challenge larger companies. Yet, it is observed by scholars that SMEs are reluctant to implement new technology tools, which leads us to question the decisive factors to either adopt or not digital marketing practices.